Efficacy and safety of ruxolitinib combined with steroids for first-line treatment of acute graft-versus-host disease after hematopoietic stem cell transplantation: a single-center, real-world experience - Yang, Yan; Huo, Yuan; Zhou, Dong; Kang, Zhijie; Huang, Yanan; Wang, Ying; Fan, Guangjun; Ma, Liyuan; Yan, Jinsong (Frontiers in Immunology, 2025)
IntroductionDespite the increasing use of allogeneic hematopoietic stem cell transplantation (allo-HSCT), graft-versus-host disease (GVHD) remains the main cause of morbidity and mortality, significantly impacting HSCT outcomes. Steroids are the standard first-line treatment for acute GVHD (aGVHD); however, standardized treatment algorithms for patients who do not respond to steroid therapy are lacking. Ruxolitinib is the most promising second-line therapy for steroid-refractory (SR)-GVHD, but data on its first-line use for aGVHD are limited.MethodsIn this retrospective study, we analyzed the data of 133 patients with aGVHD who underwent transplantation at our institution. Eighty-three patients received ruxolitinib combined with methylprednisolone, while 50 received methylprednisolone alone as the initial treatment.ResultsThe ruxolitinib/steroids group had a significantly higher overall response rate (ORR) on day 7 (86%) compared to the steroid-only group (68%; odds ratio [OR]=2.8, 95% confidence interval [CI]: 1.2–6.5, p=0.019). Similarly, ORR on day 14 was higher in the ruxolitinib/steroids group (92% vs. 79%; OR=2.7, 95% CI: 0.9–7.8, p=0.05). Although no statistical differences were observed in overall survival (OS), progression-free survival (PFS), and failure-free survival (FFS) between the two groups, patients who achieved early ORR on days 7 and 14 had better OS, PFS, and FFS. Additionally, in subgroup analysis of patients who underwent peripheral blood stem cell transplantations, the ruxolitinib/steroids cohort had significantly better OS (Hazard Ratio [HR]=0.34, 95% CI: 0.11–1.55, p=0.04), PFS (HR=0.37; 95% CI: 0.12–1.10, p=0.05) and FFS (HR=0.46; 95% CI: 0.19–1.11, p=0.05) compared to the steroid-only cohort. Adverse event (AEs) frequencies were comparable between groups, with the exception of neutropenia (32.5% vs. 12%, p=0.008) and CMV infection (34.9% vs. 18%, p=0.036), which were more frequent in the ruxolitinib/steroid group.DiscussionTo the best of our knowledge, this is the first real-world study to demonstrate that adding ruxolitinib to a standard methylprednisolone regimen provides an effective and safe first-line treatment for aGVHD.